Clinical participation of medical students in three contemporary training models. Issue 12 (December 2015) - Shahi, Rashmi; Walters, Lucie; Ward, Helena; Woodman, Richard J; Prideaux, David
Abstract : Objectives: As community settings are being used increasingly in undergraduate medical programmes, this study aimed to explore and compare the clinical experiences of students in hospital‐based and community‐based training programmes. It measured students' clinical participation and compared the perspectives of Year 3 medical students in three different models of clinical education: a tertiary hospital block programme; a community hybrid programme, and a rural longitudinal integrated clerkship (LIC) programme. Methods: The study used a mixed methodology approach to examine the clinical experiences of students through the analysis of logbooks and semi‐structured student interviews. This involved the quantitative analysis of 88 logbook weeks, data from which were triangulated through the analysis of 101 individual interviews using grounded theory. Results: A total of 35 students across the three different clinical training models participated in the study. The results demonstrate significant differences among the three models in students' clinical participation and suggest that community settings provide more opportunities to students for meaningful engagement in patient care activities. Conclusions: Consistent wider and more direct access to patients for students, as found in the community‐based model, provides a pathway for engaging students in the learning processes, and a step towards making them aware of their learning needs and knowledge. Interviews provide evidence that authentic clinical activities can be enhanced through structured systems of supervision and through the provision of authentic roles for students in clinical teams. Abstract : Discuss ideas arising from the article athttp://www.mededuc.com discuss.